From Signs to Stigma: Enregisterment and Platformed Racism in TikTok Comments - Ramadhan, Moh; Muziatun; Malabar, Fahria (Kajian Linguistik dan Sastra, 2025)
This article investigates how stigma around so-called “gang hand signs” is produced, circulated, andnegotiated in TikTok comments. Drawing on a case-bounded corpus of 675 comments posted under fivevideos from the account TopNotch Idiots (posted in 2023; comments captured in 2025), the analysisintegrates critical sociolinguistics and language-ideological perspectives with the concepts ofenregisterment and platformed racism. We operationalize a two-layer coding scheme: stigma processes(labeling, stereotyping, separation/status loss, discrimination) and sociolinguistic lenses (indexicals ofrisk, digital gatekeeping, platformed racism cues, moral-panic rhetoric). Findings show that gestures areenregistered as a default “danger register,” normalizing punitive discourse (“deserve to get hurt”);commenters perform outsider exclusion and moral boundary-making; and racialized/locational cuesalign with platformed racism, intensified by platform affordances and virality. We discuss implicationsfor critical media literacy and English language pedagogy in Indonesia, arguing that user-generateddiscourse not only mainstream media now participates in the production of stigma and public moralities.The study contributes to research on indexicality, platform governance, and digital vigilantism, andsuggests ethics-oriented classroom practices for interrogating harmful registers online.